THE THAI CANAL PROJECT: AN IMPACT ANALYSIS IN ECONOMIC, SOCIAL, AND ENVIRONMENTAL DIMENSIONS - krailassuwan, somchart (Journal of MCU Phetchaburi Review, 2025)
The Thai Canal Project, also known as the Kra Isthmus cutting, aims to connect the Andaman Sea with the Gulf of Thailand and has been studied extensively since the Ayutthaya period. This academic paper examines the project through four key dimensions: (1) historical and geographical aspects, (2) economic and international trade implications, (3) environmental and social impacts, and (4) security and geopolitical considerations. The analysis employs the Sustainable Development Goals (SDGs) framework and Critical Geopolitics theory to evaluate the project's feasibility. The findings suggest that while the initiative holds potential to transform Thailand into a global trade hub and generate substantial economic benefits, significant challenges remain, including marine ecosystem risks, political uncertainties, and competition with the Malacca Strait. The paper recommends conducting an in-depth feasibility study and establishing an international cooperation framework prior to project implementation.